Toxic Masculinity as Potrayed in Guns N Roses Songs Lyrics - Budiansyah, Muhammad Yusuf; Jamaris, Anita (JEdu: Journal of English Education, 2025)
In this life, we are confronted with various cultures that exist, and these cultures are always believed by the community to be good things. For example, the masculine culture in men or commonly referred to as toxic masculinity. This culture has been believed from generation to generation as a reference that men are a gender that must exceed women. What is believed to be toxic are narrow traditional beliefs, attitudes, practices and norms that lead men to the three main markers of power, control and violence. The research aimed to find out the toxic masculinity concepts in Guns N Roses songs. The method used in this research was qualitative research method. The data of this research were collected from Guns N Roses lyrics. In analyzing the data Kupers theory about toxic masculinity is used. After analyzing the data the researcher found 28 data that related to the toxic masculinity concept from the lyrics: 9 data of misogyny, 5 data of homophobia, 7 data of greed, and 7 data of violent domination and the type that mostly appeared of toxic masculinity in this research is misogyny.